2019
DOI: 10.1097/md.0000000000015534
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial A3243G mutation causes mitochondrial encephalomyopathy in a Chinese patient

Abstract: Rationale: Mitochondrial mutations are associated with a wide spectrum of clinical abnormalities. More than half of these mutations are distributed in the 22 mitochondrial tRNA genes, including tRNA Leu(UUR) . In particular, the A3243G mutation in the tRNA Leu(UUR) gene causes mitochondrial encephalomyopathy. Patient concerns: A 12-year-old boy was admitted to Shaoxing People's Hospital because there is a reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…One of the most common mutation among the patients with different types of mtDNA mutations is m.A8344G, which affects the mitochondrial tRNA lysine [97][98][99][100][101]. Another prominent mutation in the same gene is m.G8363A, along with the m.A3243G, m.G3255A, and m.T3291C mutations, which have also been reported to cause MERRF with a defects in tRNA leucine [57][58][59]99,102,103]. Mutations in tRNA-coding genes induce the global impairment of mtDNA-encoded proteins rather than affecting certain complexes or pathways [101,104,105].…”
Section: Neurological Symptoms Cardiac Dysfunction Dyspraxiamentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most common mutation among the patients with different types of mtDNA mutations is m.A8344G, which affects the mitochondrial tRNA lysine [97][98][99][100][101]. Another prominent mutation in the same gene is m.G8363A, along with the m.A3243G, m.G3255A, and m.T3291C mutations, which have also been reported to cause MERRF with a defects in tRNA leucine [57][58][59]99,102,103]. Mutations in tRNA-coding genes induce the global impairment of mtDNA-encoded proteins rather than affecting certain complexes or pathways [101,104,105].…”
Section: Neurological Symptoms Cardiac Dysfunction Dyspraxiamentioning
confidence: 99%
“…This can result in the overall dysfunction of mitochondria. In case studies involving MERRF patients with tRNA lysine mutations, various symptoms were reported, such as unsteadiness of gait, optic atrophy, slurred speech, sensorineural hearing loss, and limb weakness [57][58][59].…”
Section: Neurological Symptoms Cardiac Dysfunction Dyspraxiamentioning
confidence: 99%
“…Oxiracetam is a drug used for the clinical treatment of cognitive dysfunction after stroke. Nevertheless, despite the effectiveness of oxiracetam in enhancing the restoration of brain tissue function in stroke patients, the drug is associated with adverse reactions, leading to poor treatment compliance [5,6].…”
Section: Introductionmentioning
confidence: 99%